Transcriptome-Wide Identification of Nine Tandem Peptide Repeat Families in Roselle (Hibiscus sabdariffa L.) - Christina Seok Yien Yong; Nur Atheeqah-Hamzah (Tropical Life Sciences Research, 2024)
Plants are rich in tandem repeats-containing proteins. It is postulated that the occurrence of tandem repeat gene families facilitates the adaptation and survival of plants in adverse environmental conditions. This study intended to identify the tandem repeats in the transcriptome of a high potential tropical horticultural plant, roselle (Hibiscus sabdariffa L.). A total of 92,974 annotated de novo assembled transcripts were analysed using in silico approach, and 6,541 transcripts that encoded proteins containing tandem repeats with length of 20–60 amino acid residues were identified. Domain analysis revealed a total of nine tandem repeat protein families in the transcriptome of roselle, which are the Ankyrin repeats (ANK), Armadillo repeats (ARM), elongation factor-hand domain repeats (EFhand), Huntingtin, elongation factor 3, protein phosphatase 2A, yeast kinase TOR1 repeats (HEAT), Kelch repeats (Kelch), leucine rich repeats (LRR), pentatricopeptide repeats (PPR), tetratricopeptide repeats (TPR) and WD40 repeats (WD40). Functional annotation analysis further matched 6,236 transcripts to 1,045 known proteins that contained tandem repeats including proteins implicated in plant development, protein-protein interaction, immunity and abiotic stress responses. The findings provide new insights into the occurrence of tandem repeats in the transcriptome and lay the foundation to elucidate the functional associations between tandem peptide repeats (TRs) and proteins in roselle and facilitate the identification of novel biotic and abiotic response related tandem repeats genes that may be useful in breeding improved varieties.